TRANSLATION STRATEGIES IN THE CONTENT LOCALIZATION OF AGODA.COM - Diana, Sayra Nuraflah; Mono, Umar; Br. Perangin-angin, Alemina (Universitas Islam Sumatera Utara (UISU), 2024)
This study aims to analyze the translation strategies used in the content localization of Agoda.com, an online travel agency website, in both English and Bahasa Indonesia. Data collection was conducted through documentation, involving screenshots of specific content on Agoda.com. The collected data were categorized according to the framework proposed by Singh et al. (2009) and analyzed using Pierini's (2007) theory on website translation strategies. The research employed a mixed-methods approach, combining quantitative and qualitative analyses, supplemented by documentation and note-taking techniques. The findings reveal that the predominant translation strategy applied in Agoda.com’s content localization is full translation, accounting for 45% of the data samples (82 instances). This is followed by modified translation with 31.9% (58 instances), partial translation with 14.8% (27 instances), and rewritten translation with 7.7% (14 instances).